Maturational differences in lung NF-κB activation and their role in tolerance to hyperoxia - Yang, Guang (American Society for Clinical Investigation, 2004)
Neonatal rodents are more tolerant to hyperoxia than adults. We determined whether maturational differences in lung NF-κB activation could account for the differences. After hyperoxic exposure (O(2) > 95%), neonatal (<12 hours old) lung NF-κB binding was increased and reached a maximum between 8 and 16 hours, whereas in adults no changes were observed. Additionally, neonatal NF-κB/luciferase transgenic mice (incorporating 2 NF-κB consensus sequences driving luciferase gene expression) demonstrated enhanced in vivo NF-κB activation after hyperoxia in real time. In the lungs of neonates, there was a propensity toward NF-κB activation as evidenced by increased lung I-κB kinase protein levels, I-κBα phosphorylation, β-transducin repeat–containing protein levels, and total I-κBα degradation. Increased lung p-JNK immunoreactive protein was observed only in the adult lung. Inhibition of pI-κBα by BAY 11-7085 resulted in decreased Bcl-2 protein levels in neonatal lung homogenates and decreased cell viability in lung primary cultures after hyperoxic exposure. Furthermore, neonatal p50-null mutant (p50(–/–)) mice showed increased lung DNA degradation and decreased survival in hyperoxia compared with WT mice. These data demonstrate that there are maturational differences in lung NF-κB activation and that enhanced NF-κB may serve to protect the neonatal lung from acute hyperoxic injury via inhibition of apoptosis.